2015
DOI: 10.1002/jctb.4625
|View full text |Cite
|
Sign up to set email alerts
|

The usage of different forms of ferrate (VI) ion for amoxicillin and ciprofloxacin removal: density functional theory based modelling of redox decomposition

Abstract: BACKGROUND: Decomposition of amoxicillin (AMX) and ciprofloxacin (CIP) in aqueous suspensions by two forms of ferrate (VI) were investigated. The effect of the initial concentration of antibiotics, pH, and ferrate (VI) dosage were examined. Model calculations were made by the Density Functional Theory (DFT) method (RB3LYP) taking into account the environmental parameters. LanL2DZ and 6-311G

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Accordingly, there is increasing interest to develop efficient treatment processes for controlling the occurrence of pharmaceutical pollutants in aquatic bodies. Advanced oxidation processes (AOPs) have been used widely to remove pharmaceutical compounds such as ozonation [8][9][10][11], ferrate (VI) [12,13], photocatalysis [14][15][16] and electrochemical oxidation [17,18]. Chemical oxidation with ozone is an efficient technology for the removal of organic pollutants, but the performance is often not strong enough due to its selectivity to remove some target pollutants in a realistic time and cost frame.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there is increasing interest to develop efficient treatment processes for controlling the occurrence of pharmaceutical pollutants in aquatic bodies. Advanced oxidation processes (AOPs) have been used widely to remove pharmaceutical compounds such as ozonation [8][9][10][11], ferrate (VI) [12,13], photocatalysis [14][15][16] and electrochemical oxidation [17,18]. Chemical oxidation with ozone is an efficient technology for the removal of organic pollutants, but the performance is often not strong enough due to its selectivity to remove some target pollutants in a realistic time and cost frame.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the powder is dispersed in non-volatile liquid paraffin (Nujol) that has low absorption in the infrared region. FT-IR provides a primary peak for ferrate salt around 808 cm -1 and a shoulder peak can also be observed approximately at 780 cm -1 , which point out to the asymmetric stretching vibrations of the ironoxygen bond in the ferrate(VI) compound [74]. The more the intensity of the characteristic vibrational peak of ferrate(VI) is strong, more the purity of the prepared ferrate(VI) is also higher.…”
Section: Fourier Transform-infrared (Ft-ir) Spectroscopymentioning
confidence: 91%
“…When used as a disinfectant, studies have shown that ferrate(VI) salt is more effective than chlorine in reducing different types of bacteria and viruses [37,78]. Furthermore, ferrate(VI) has been used to control odour, to remove pharmaceutical pollutants such as amoxicillin, ciprofloxacin, 2,4-dichlorophenoxyacetic acid, and flurbiprofen from wastewater [74], to stabilise and dewater primary sludge [83], and to remove freshwater humic substances from water [84].…”
Section: Application Of Ferrate(vi) Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, numerous methods have been studied for the removal of antibiotic CIP from aquatic environments. Among the most common methods are adsorption, ozonation, and photocatalytic processes (7,8). Considering the costliness and production of intermediate products by the abovementioned methods, biological processes have attracted a great deal of attention thanks to being environment friendly and not needing advanced facilities (9).…”
Section: Introductionmentioning
confidence: 99%